Evaluation Of Different Mutagens Against Fusarium Oxysporum F. Sp. Ciceri, Causing Chickpea Wilt (Journal of Plant Disease Sciences, 2021)
Fusarium wilt, caused by Fusarium oxysporum f. sp. ciceri (Foc) is one of the most important fungal diseases of chickpea, limiting its productivity in nearly all chickpea- growing countries worldwide. The purpose of this study was to investigate the possibility of identifying wilt resistant chickpea genotypes using gamma rays and EMS as a novel technique. Induced mutagens cultivars further subjected to the field screening and water culture technique. The test mutagens had the greatest impact on the chickpea cultivar Vijay, followed by JG-62, BDNG 798, and JAKI 9218. Cultivar JG 62 was found to be highly susceptible, with a wilt incidence ranging from of 97.35 to 100%. Cultivars Vijay and BDNG 798 showed resistant and moderately resistant reactions to wilt disease in both screening techniques, whereas cv. JAKI 9218 showed moderately resistant and moderately susceptible reactions.
Keywords: Chickpea; Fusarium oxysporum f. sp. ciceri; Mutagens; Screening